SOME ASPECTS OF ACCOUNTING EDUCATION. - Meyer, Harvey G. (The Accounting Review, 1961)
Accounting education has burgeoned almost out of control, and it is small wonder that it has been subject to so much questioning. There is little discussion of theory either by the instructor or by the students. The "why" is subordinated to the "how." Students are not encouraged to understand, to apply their knowledge to differing situations, or to use accounting as a tool rather than as an end in itself. Instructors sometimes are lazy, or preoccupied with graduate work, or spend considerable time on outside engagements. Sometimes instructors do not take an interest in their students or their problems. They have too many students and a student tends to become a statistic or a name in the gradebook, rather than an individual human being. Many students are of average ability, but regardless of ability their attitudes toward effort and hard work are not strengthened or stimulated by the environment of the college or the accounting classroom. The author concludes that most significant problems in accounting profession do not grow out of the deficiencies as many institutions, instructors, and students are meeting these challenges. But the problems grow out of diversities.